2016
DOI: 10.14507/epaa.24.2768
|View full text |Cite
|
Sign up to set email alerts
|

Locating and applying critical discourse analysis within education policy

Abstract: This article introduces the first of a two-part Special Issue on Discourse Perspectives and Education Policy. This first special issue is focused on critical discourse analysis and education policy. Within this article, we provide a brief overview of discourse analysis generally and critical discourse analysis specifically. We highlight some of the ways in which policy researchers have applied the theories and methods associated with CDA and note the methodological and substantive contributions of this work. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 14 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…Finally, we employ discourse analysis in order to develop a deeper understanding of the themes and messages conveyed in the policy frameworks and statements. Several previous studies have demonstrated that discourse analysis and critical discourse analysis can be effective tools for the analysis of educational practices and policies (Lester, Lochmiller, & Gabriel, 2016Liasidou, 2008;Rogers et al, 2016;Taylor, 2004). Discourse analysis, according to van Dijk (1993), seeks to understand "the role of discourse in the (re)production and challenge of dominance [italics in original]" in order to draw out the deeper meanings and relationships represented in the policy statements (p. 283).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we employ discourse analysis in order to develop a deeper understanding of the themes and messages conveyed in the policy frameworks and statements. Several previous studies have demonstrated that discourse analysis and critical discourse analysis can be effective tools for the analysis of educational practices and policies (Lester, Lochmiller, & Gabriel, 2016Liasidou, 2008;Rogers et al, 2016;Taylor, 2004). Discourse analysis, according to van Dijk (1993), seeks to understand "the role of discourse in the (re)production and challenge of dominance [italics in original]" in order to draw out the deeper meanings and relationships represented in the policy statements (p. 283).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, qualitative policy analysis, has relied heavily on interview data in order to describe and explain the normative experiences of how policy becomes developed, implemented, and lived out by those affected by it (Lester, Lochmiller, & Gabriel, 2016). These normative explanations have been extremely useful in providing landscape views of policy regimes in education.…”
Section: A Few Notes On Education Policy and Methodologymentioning
confidence: 99%
“…The notions of discourse as Foucault's conduct of conducts referenced earlier, and the recognition that policy texts can generate new political relations as well as augment or re-arrange cultural understandings are clear derivations from Foucauldian theorizations of neoliberalism and the genealogies of contemporary history. I enjoin these poststructural building blocks of third generation policy analysis (Lester, Lochmiller, & Gabriel, 2016), to the ontological project of post-qualitative research, building upon the philosophies referenced earlier.…”
Section: "Analysis" or Some Ways Of Cutting Throughmentioning
confidence: 99%